A Comparison of Love Views in a Dream of Red Mansions and Romeo and Juliet - Lin, Zhiqi (Journal of Ecohumanism, 2024)
The view of love is the essence of artistic and artistic creation of literary works. In the development of Chinese and western cultural works, a lot of literary works in line with the cultural view have been born. A Dream of Red Mansions and Romeo and Juliet are typical masterpieces of Chinese and Western literature, both of which express the yearning for beautiful love, but they are both presented in the way of love tragedy, and also reflect different views of love and social outlook. Chinese and western literary works are different in language, aesthetic appreciation, characters, values and other aspects, showing the cultural characteristics of different regions, better revealing the differences between Chinese and western love concepts, and improving the artistic aesthetic value of literary works. In Chinese and western literary works, influenced by social concepts, cultural differences between Chinese and western countries, the views of love in literary works also have certain differences, and there are also differences in the ways and ideas of pursuing love, so as to show love stories under different social backgrounds. In this paper, the Chinese and Western literary works of A Dream of Red Mansions and Romeo and Juliet are the research objects, and discuss the differences of love views between Chinese and Western literature from the aspects of love stories, characters and love concepts, so as to bring better guidance and reference for the high-quality development of Chinese literary works.